Digital Waqf: transforming the Islamic economy in the Modern Era - Rupita, Nanda Ega; Afifah, Dhiya Dwi (MUI Kota Pekanbaru, 2024)
Digital waqf is an innovation in Islamic philanthropy leveraging modern technology to optimize waqf fund management. This study aims to explore the opportunities and challenges of digital waqf and its contribution to wealth redistribution and Islamic economic development. The research employs a literature review method, analyzing various studies on digital waqf and supporting technologies like blockchain. The results indicate that digital waqf enhances efficiency, transparency, and public participation, particularly through digital platforms. However, challenges such as low digital literacy, limited infrastructure, and inadequate regulations hinder the optimization of its potential. This study recommends improving digital literacy, establishing comprehensive regulations, and fostering collaboration among governments, Islamic financial institutions, and fintech to build an inclusive and sustainable digital waqf ecosystem.